2013
DOI: 10.2215/cjn.05540512
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomic Profiles in Different Stages of CKD

Abstract: SummaryBackground and objectives CKD is a common public health problem. Identifying biomarkers adds prognostic/ diagnostic value by contributing to an understanding of CKD at the molecular level and possibly defining new drug targets. Metabolomics provides a snapshot of biochemical events at a particular time in the progression of CKD. This cross-sectional metabolomics study ascertained whether plasma metabolite profiles are significantly different in CKD stages 2, 3, and 4.Design, setting, participants, & mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 37 publications
5
68
0
2
Order By: Relevance
“…For example, N-acetylalanine was negatively associated with eGFR CKD-EPI , having the lowest P value in this study, and Toyohara et al (19) reported N-acetylalanine to be a uremic retention anion. Another cross-sectional study of 30 participants, with 10 patients each in CKD stages 2-4, showed significant differences of plasma metabolites among various stages of CKD (20). In the study, 3-carboxy-4-methyl-5-propyl-2-furanpropanoate, a known uremic toxin, was higher in CKD stages 3 and 4 compared with CKD stage 2.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, N-acetylalanine was negatively associated with eGFR CKD-EPI , having the lowest P value in this study, and Toyohara et al (19) reported N-acetylalanine to be a uremic retention anion. Another cross-sectional study of 30 participants, with 10 patients each in CKD stages 2-4, showed significant differences of plasma metabolites among various stages of CKD (20). In the study, 3-carboxy-4-methyl-5-propyl-2-furanpropanoate, a known uremic toxin, was higher in CKD stages 3 and 4 compared with CKD stage 2.…”
Section: Discussionmentioning
confidence: 81%
“…These technologies create an opportunity to investigate both the effect of kidney function on the metabolome and the ability of metabolomic measures to predict the onset of incident CKD (17). Several studies have shown that metabolic profiles can uncover potential biomarkers related to eGFR and different stages of CKD in multiple ethnicities (18)(19)(20)(21). A recent study has reported that adding metabolomic predictors of renal function independent of eGFR to clinical data may significantly improve the ability to predict onset of CKD among European Americans (17).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing interest has been directed toward the application of metabolite profiling to plasma from individuals with existing CKD or ESRD. [2][3][4][30][31][32] Here, we profile plasma obtained from individuals up to 8 years before disease onset, on the principle that non-GFR markers of renal metabolite handling may be sensitive indicators of incipient kidney dysfunction. Although metabolite profiling alone may not be sufficiently specific to identify individuals who go on to develop CKD, it may contribute to clinical models of CKD prediction that contain other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney dysfunction is associated with an increase in inflammatory and procoagulant biomarkers, including C-reactive protein, fibrinogen, factor VII, and factor VIII 13,14 and has been considered a marker of organ damage caused by hypertension or diabetes mellitus.…”
Section: Risk Of Stroke and Bleeding Associated With Reduced Egfrmentioning
confidence: 99%